2016
DOI: 10.1089/can.2015.0004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Psychoactive Degradants of Cannabidiol in Simulated Gastric and Physiological Fluid

Abstract: Introduction: In recent research, orally administered cannabidiol (CBD) showed a relatively high incidence of somnolence in a pediatric population. Previous work has suggested that when CBD is exposed to an acidic environment, it degrades to Δ9-tetrahydrocannabinol (THC) and other psychoactive cannabinoids. To gain a better understanding of quantitative exposure, we completed an in vitro study by evaluating the formation of psychoactive cannabinoids when CBD is exposed to simulated gastric fluid (SGF).Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 31 publications
(51 reference statements)
2
78
3
2
Order By: Relevance
“…Drugs CBD was administered transdermally to enhance translational relevance regarding future therapeutic applications. The clinical potential of CBD when administered orally is constrained to some extent by low (~6%) bioavailability [28] and potential for conversion into psychoactive cannabinoids in gastric fluid [29]. However, we have identified the transdermal route of administration as an effective delivery method that eliminates both these limitations and produces stable and sustained plasma CBD levels [26,30].…”
Section: Methodsmentioning
confidence: 99%
“…Drugs CBD was administered transdermally to enhance translational relevance regarding future therapeutic applications. The clinical potential of CBD when administered orally is constrained to some extent by low (~6%) bioavailability [28] and potential for conversion into psychoactive cannabinoids in gastric fluid [29]. However, we have identified the transdermal route of administration as an effective delivery method that eliminates both these limitations and produces stable and sustained plasma CBD levels [26,30].…”
Section: Methodsmentioning
confidence: 99%
“…Specific strains of cannabis may also produce high levels of a second phyto-CB, cannabidiol (CBD), often referred to as non-psychoactive. Although not associated with cannabis-induced euphoria or intoxication (Grotenhermen et al, 2017), CBD exposure is psychoactive and affects several brain functions and behaviors, including neuronal activity, seizure incidence and social interactions (Renard et al, 2017a; Todd and Arnold, 2016). Accordingly, CBD has been linked to influencing a wide range of clinical outcomes such as epilepsy and neuropsychiatric disorders.…”
Section: What Is Cannabis?mentioning
confidence: 99%
“…shown that orally administered CBD may degrade into the psychoactive THC in simulated gastric fluids containing 1% SDS (Watanabe 2007, Merrick 2016. More recently, these in vitro results have been called into question as there is no in vivo evidence to support these claims (Russo 2017, Vitality Bio unpublished results).…”
Section: Discussionmentioning
confidence: 99%